Dimensions of Normal Coronary Arteries in a Tertiary Cardiac Center Kathmandu - Sharma, Padam PD; Poudel, Chandra M; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Khanal, Rajaram; Shakya, Smriti; Thapa, Shovit; Gajurel, Ratna M (Journal of Institute of Medicine Nepal, 2023)
Introduction Coronary artery disease is the major cause of morbidity and mortality worldwide. The knowledge of normal coronary artery dimensions is fundamental during the percutaneous coronary intervention for appropriate sizing of the coronary balloons and stents. The dimensions of the coronary arteries differs among individuals of various countries, even among the different ethnicities. So, this study wass done to find out the normal coronary artery dimensions. Methods This study was done in randomly selected 100 normal coronary angiograms. The diameter and the length of different segments of coronary artery were measured with the use of software as quantitative coronary angiography. Results Mean diameter of left main (LM) coronary artery was 4.06±0.68 mm. Similarly, mean diameters of prox-left anterior descending (LAD) artery, mid-LAD, dist-LAD, prox-left circumflex (LCx) artery and dist-LCx were 3.26±0.48 mm, 2.67±0.49 mm, 2.01±0.44 mm, 2.91±0.48 mm and 2.38±0.44 mm respectively. And, the mean diameters of prox-right coronary artery (RCA), mid-RCA and dist-RCA were 3.2±0.51 mm, 2.89±0.5 mm and 2.43±0.51 mm respectively. The mean lengths of LM, proximal/mid and distal LAD were 10.06±3.12 mm, 17.91±6.09 mm, 18.28±6.81 mm, 67.94±15.57 mm respectively. The mean lengths of proximal and distal LCX were 18.95±10.13 mm, and 52.1±17.78 mm respectively. Similarly, the mean lengths of proximal, mid, and distal RCA were 17.2±4.74 mm, 33.82±9.4 mm, 33.43±12.01 mm respectively. The mean diameter and mean length of ramus intermedius (RI) was 2.32±0.56 mm and 70.77±19.75 mm. Conclusion LM artery and p-RI had the largest and the smallest diameters respectively. LAD and RI had the longest and the shortest courses respectively.